A Place at the End of a Road: A Yin-Yang Geography - Farquhar, Judith; Lai, Lili; Kramer, Marshall (Anthropologica, 2017)
If one task of modern nation-states is to produce a commons or a known universe, a one-world world that is visible to all, what spaces are left for the uncommons? Drawing on a 2014 visit to a village, once a county town, just barely within the borders of China, we follow James Scott in asking not only how a state sees but what a state might be able to see, as well. To understand the uncanny (in)visibility of this place, we invoke Chinese yin-yang theory to reflect on the ways that human space transforms through time, partly hidden by yin shade and partly revealed in yang glare. The uncommons is not, in other words, an exterior to the one-world world; rather, it is a possible world that can make itself partly known in a mottled and ever-changing light and shade.